PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR PERTAMBANGAN TAHUN 2017-2021 - Gusti Agung Mirah Arinda; Eka Putri Suryantari; Ni Luh Putu Sri Purnama Pradnyani (Universitas Triatma Mulya, 2022)
Tax payments by tax subjects are a source of income for the state which will be used as a source of financing development activities. On the other hand, tax is a deduction from the company's profit so that this difference in interests triggers certain ways created by the company both legally and illegally in reducing the taxes paid. One of the ways taken by the company is tax avoidance. The purpose of this study was to determine the effect of profitability, firm size and capital intensity on tax avoidance. This research was conducted on mining sector companies listed on the Indonesia Stock Exchange in 2017-2021 with a total sample of 19 companies. Sample selection was done by purposive sampling and data collection was done by documentation. The results show that partially the three independent variables have a positive effect on tax avoidance, this means that the higher profitability, firm size and capital intensity will increase tax avoidance in the companies studied